Draft genome sequence of a human-associated streptogramin-resistant Staphylococcus aureus. (March 2019) - Gupta, Sushim K.; Sharma, Poonam; Barrett, John B.; Hiott, Lari M.; Woodley, Tiffanie A.; Frye, Jonathan G.; Jackson, Charlene R.
Abstract: Objectives: Staphylococcus aureus is one of the leading causes of nosocomial and community-acquired infections. Treatment of these infections with macrolide–lincosamide–streptogramin (MLS) antibiotics has led to resistance to these antibiotics via various mechanisms. S. aureus strain CIP108540, isolated from a human in France, has been previously shown to exhibit resistance to the streptogramins quinupristin and dalfopristin; the presence of streptogramin resistance genes was verified by PCR. However, the extent of MLS resistance genes in this strain is unknown. This study analysed the genome sequence of S. aureus CIP108540 to assess genes associated with antimicrobial resistance, including to streptogramins. Methods: Genomic DNA of S . aureus CIP108540 was sequenced using Illumina MiSeq. The generated sequencing reads were de novo assembled using A5-miseq. Results: The draft genome size was 3 014 273 bp with a GC content of 32.72%. There were 3063 predicted coding sequences with 59 tRNAs. Several antimicrobial resistance genes were identified conferring resistance to various antibiotics. Conclusion: The draft genome sequence of S. aureus CIP108540 released here will provide valuable information for a better understanding of its genetic makeup and resistome.